Testing the Power of Exchange Rate to Equalize Prices - Adhikari, Deergha Raj (Journal of Applied Business and Economics, 2016)
Although already been tested numerous times thus far, researchers are still fascinated by the purchasing power parity (PPP) hypothesis due to its implication for international trade and financial flows, which stipulates that the exchange rate between any two currencies changes to equalize the price levels (purchasing power) in the two countries. This hypothesis has been tested by mainly testing the stationarity of the real exchange rate between any two currencies of interest. But we use a different approach. Our model is based on the long-term relationship between the official exchange rate and the relative inflation rates between two countries. According to our model, the validity of the PPP hypothesis is based on the non-rejection of the null hypotheses that the intercept term in the regression of the official exchange rate on the relative inflation rate is equal to zero and that the coefficient associated with the relative inflation rate is equal to one. We applied our test on a panel data from five BRICS countries. Our results rejected both null hypotheses at 5% significance level. Thus our findings invalidate the PPP hypothesis.